Influence of Pre- and Post-Drought Application of Thiourea on Growth, Net Photosynthesis and Nitrogen Metabolism of Clusterbean - Burman, Uday; Garg, B K; Kathju, S (Annals of Arid Zone, 2016)
Clusterbean (Cyamopsis tetragonoloba (L.) Taub.) plants, grown with and without thiourea (seed treatment with 500 ppm + one foliar spray with 1000 ppm of thiourea at 28 days after sowing), were subjected to moderate (5 days drought) and severe water stress (10 days drought) at the critical pre-flowering stage (40 DAS) where well-watered plants served as control. After 4 days of rewatering one set of plants under each treatment was sprayed with 1000 ppm thiourea and another with water, to study the post-drought effects of thiourea application. Thiourea pre-plants maintained higher relative water content, net photosynthesis, levels of different leaf metabolites and nitrate reductase (NR) activity than control plants under all intensities of water stress. The recovery of all the above-mentioned parameters on rewatering was also better in thiourea-than control plants. Furthermore, post-drought foliar spray of thiourea resulted in higher levels of total chlorophyll, starch, soluble protein, NR activity and net photosynthesis as compared to water- sprayed plants one week after their application. This led to significantly higher seed yield and shoot dry matter production in thiourea-applied plants even after the drought event. Results also revealed that pre- and post-drought application of thiourea displayed additive effects on plant performance and yield due to cumulative favorable effects on leaf metabolism and photosynthesis .. Key words: Clusterbean, thiourea, foliar spray, net photosynthetic rate, nitrate reductase, water stress.